Horizontal transfer and phylogenetic distribution of the immune evasion factor tarP - Gerlach, David; Sieber, Raphael N.; Larsen, Jesper; Krusche, Janes; De Castro, Cristina; Baumann, Juliane; Molinaro, Antonio; Peschel, Andreas (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA), a major human pathogen, uses the prophage-encoded tarP gene as an important immune evasion factor. TarP glycosylates wall teichoic acid (WTA) polymers, major S. aureus surface antigens, to impair WTA immunogenicity and impede host defence. However, tarP phages appear to be restricted to only a few MRSA clonal lineages, including clonal complexes (CC) 5 and 398, for unknown reasons. We demonstrate here that tarP-encoding prophages can be mobilized to lysogenize other S. aureus strains. However, transfer is largely restricted to closely related clones. Most of the non-transducible clones encode TarM, which generates a WTA glycosylation pattern distinct from that mediated by TarP. However, tarM does not interfere with infection by tarP phages. Clonal complex-specific Type I restriction-modification systems were the major reasons for resistance to tarP phage infection. Nevertheless, tarP phages were found also in unrelated S. aureus clones indicating that tarP has the potential to spread to distant clonal lineages and contribute to the evolution of new MRSA clones.